Mangrove plants species from Delta Mahakam, Indonesia with antimicrobial potency - GINA SAPTIANI; ANDI NOOR ASIKIN; ESTI HANDAYANI HARDI; FIKRI ARDHANI (Society for Indonesian Biodiversity, 2018)
Saptiani G, Asikin AN, Ardhani F, Hardi EH. 2018. Mangrove plants species from Delta Mahakam, Indonesia with antimicrobial potency. Biodiversitas 19: 516-521. This research was aimed to study biodiversity of mangrove that have potential as an antimicrobial material. The leaves of 4 types of mangroves, namely Avicennia marina, Sonneratia alba, Rhizophora stylosa, and Acanthus ilicifolius were chopped, dried and extracted with 3 types of solvents 80% ethanol, water and seawater. The Antimicrobial used Agar Disc Diffusion (ADD) method, and Minimal Inhibitory Concentration (MIC). Microbes that used for the test were Staphylococcus aureus, Escherichia coli, Vibrio harveyi, Aeromonas hydrophila and Saprolegnia sp. The ADD test showed ethanol extract of A. marina and A. ilicifolius can inhibit S. aureus with inhibition zone 13.33±0.58 mm. All the extract can inhibit A. hydrophila 13.00±1.00 mm and E. coli 12.67±0.58 mm. Ethanol extract of S. alba can inhibit V. harveyi 12.67±0.58 mm and A. ilicifolius 12.33±0.58 mm against Saprolegnia sp. The best of MIC is ethanol extract of A. ilicifolius, following A. marina, S. alba and R. stylosa.